Local earthquake seismic tomography of the Southernmost Mariana subduction zone - Dong Li; Dong Li; Chuanxu Chen; Shiguo Wu (Frontiers in Marine Science, 2023)
We employed seismic tomography to examine the velocity structure of the upper mantle in the Southernmost Mariana subduction zone. Our study focuses on data collected during a six-month experiment from 15 December 2016 to 12 June 2017, using 11 ocean bottom seismometers. By examining over 3700 local arrival times, we are able to determine the three-dimensional Vp and Vs structure. The subducting slab in this region displays a P- and S-wave velocity 2~6% higher than normal mantle and a lower Vp/Vs, with an average dip of 45° at depths ranging from 50 to 100 km. Additionally, our velocity images also shed new lights to the velocity anomalies of the mantle wedge region on top of the subducting slab, from the trench to the remnant arc. We observed slower velocity anomalies in the mantle wedge beneath the Southwest Mariana Rift, the West Mariana Ridge, and the forearc. In the outer forearc, a low-velocity anomaly is observed at depths shallower than 50 km, indicating mantle serpentinization and the presence of water. Additionally, a melt production region is observed beneath the central part of the forearc block at a depth of 40–60 km suggesting the possibility of melting processes in this region.